Fracture of the frontal sinus: complexity of multidisciplinary treatment - Vasconcelos, Vinicius Arruda; Pereira, Lucas Cavalieri; Coral, Ana Julia; Diaz, Laura; Prado, Bruno Nifossi (Frontiers in Surgery, 2026)
ObjectiveThis study aims to retrospectively analyze the management of frontal sinus fractures by a single Oral and Maxillofacial Surgery (OMFS) team over an 8-year period, underscoring epidemiological characteristics, treatment strategies, and clinical outcomes.MethodsMedical records of patients diagnosed with and treated for frontal sinus fractures between 2017 and 2024 at Piracicaba, São Paulo, Brazil, were reviewed. Data collection included demographic information, etiology, associated injuries, treatment modality, operative time, and complications. All patients underwent computed tomography (CT) evaluation, and treatment decisions followed a standardized institutional algorithm.ResultsA total of 40 patients (39 male, 1 female; mean age 42.9 years) were included. Traffic accidents were the most common cause (37.5%) of injury. Twenty-two patients (55%) were managed conservatively, while 18 (45%) underwent surgery. The mean operative time was 3 h, with a mean interval of 5 days between trauma and surgery. No intraoperative or postoperative complications were reported. The average hospital stay ranged from 3 to 7 days, depending on the presence of associated injuries.ConclusionsFrontal sinus fractures are challenging injuries that require careful assessment of displacement, nasofrontal duct patency, and patient condition to determine the optimal management approach. Conservative treatment proved effective for non-displaced fractures with a patent nasofrontal duct, whereas surgical intervention was required for displaced or comminuted fractures and provided satisfactory outcomes with minimal morbidity. These findings reinforce the importance of standardized decision-making protocols and multidisciplinary collaboration in optimizing patient prognosis.